Cytopathologic Features of Pleomorphic Carcinoma of the Lung: Case Report - Dagli, Adile Ferda; Ucer, Ozlem (De Gruyter Open Ltd, 2012)
Pleomorphic carcinoma of the lung is a subtype of sarcomatoid carcinoma and essentially classified as a poorly-differentiated, non-small cell lung carcinoma. Being a very rare tumor, it constitutes 0.3-1.3% of all malignancies of the lung. Cytology reveals malignant fusiform and/or giant cells, accompanied by malignant epithelial elements like squamous cell, adeno or large cell carcinoma. Our case, a 76-year-old female patient, presented with chest and back pain. Thoracic CT showed a well-demarcated solid mass of 5x3 cm located peripherally in the left upper lobe of the lung. Trans-thoracic fine needle aspiration cytology showed atypical cells with a biphasic character in a myxoid matrix. It was noted that of these, some were poorly-demarcated fusiform cells with oval nuclei and marked nucleoli, while others were epithelial cells with eccentrically placed nuclei, large cytoplasms and macronucleoli. The patient was diagnosed as pleomorphic carcinoma on the basis of these findings, and the cytological diagnosis was confirmed by histopathology. Pleomorphic carcinoma is a poorly-differentiated non-small cell lung carcinoma, which poses diagnostic difficulties. As it is rare, it lacks decisive diagnostic criteria and has cytological characteristics resembling those of other lung tumors.
Akci?erin pleomorfik karsinomunun sitopatolojik özellikleri: Olgu sunumu
Keywords: Lung; Pleomorphic carcinoma; Cytological diagnosis